Efficacy of Short Course Antibiotic Prophylaxis in Surgical Treatment of Closed Fracture - Jha, Subash Chandra; Baral, Pramod; Shakya, Prakash (Birat Journal of Health Sciences, 2019)
Introduction: Unnecessary and rampant use of antibiotic for perioperative prophylaxis are not only increasing cost of treatment but also are hazardous in terms of increasing antibiotic resistance, super infection with resistant pathogens and antibiotic toxicity.Objective: Our primary objective is to assess the efficacy of short course antibiotic prophylaxis in preventing surgical site infection (SSI) in surgery of closed orthopedic fracture.Methodology: Patients fulfilling all the inclusion criteria and willing and able to give informed consent were included in the study. All participants were treated by standard surgical technique following standard surgical protocol. Short course antibiotic prophylaxis was administered in peri-operative period to all patients in given format: Three divided dose of intravenous 1.5 gram cefuroxime during peri-operative period followed by no intravenous or oral antibiotics; 1st dose half an hour before incision; 2nd and 3rd dose repeated at 12 hours interval.Results: Of total 100 patient included, three developed surgical site infection till one year follow-up. All three patients with surgical site infection were treated successfully with intravenous antibiotic based on the culture sensitivity report. The average cost of antibiotic for short course antibiotic prophylaxis was 1500 NPR for each patient.Conclusions: There was no significant increase in rate of surgical site infection with short course antibiotic prophylaxis, rather it was less expensive and may have less adverse effect, in terms of antibiotic resistance and antibiotic side effects on long run.